2018
DOI: 10.18203/issn.2455-4510.intjresorthop20180511
|View full text |Cite
|
Sign up to set email alerts
|

Functional and radiological evaluation of surgical management in tibial plateau fractures: a prospective study

Abstract: <p class="abstract"><strong>Background:</strong> <span lang="EN-IN">Tibial plateau fractures affect knee which is a major weight bearing joint, altering its contribution to stability and its function. Regardless of the advancements in technique and implants, ideal mode of management is still contentious.</span></p><p class="abstract"><strong>Methods:</strong> <span lang="EN-IN">This prospective study reviewed 20 consecutive cases of tibial plateau fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In general, conservative treatment cannot exert obvious therapeutic effects, while surgery is carried out more commonly under the premise of classified fractures that are of great significance to determining the selection of appropriate surgical approaches [ 4 , 16 19 ]. Therefore, a new means of fracture classification resorted by the latest three-dimensional imaging technology is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…In general, conservative treatment cannot exert obvious therapeutic effects, while surgery is carried out more commonly under the premise of classified fractures that are of great significance to determining the selection of appropriate surgical approaches [ 4 , 16 19 ]. Therefore, a new means of fracture classification resorted by the latest three-dimensional imaging technology is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by the Swarup et al (2016) observed that out of 60 study participant, 78% were males & 22% were females. A study conducted by the Jakinapally et al (2018) observed that out of 20 study participants, 15 (75%) were males and ive (25%) were females. A study conducted by the Manikandan and Saravanakumar (2019) observed that study participants include 70% of males & 30% females.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by the Swarup et al (2016) observed that out of 60 study participants inal end result as per Rasmussen's criteria was excellent in 37, good in 11, fair in six and poor in six patients. A study conducted by the Jakinapally et al (2018) observed that nine (45%), cases had excellent outcome, seven (35%) cases had a good outcome, three (15%) cases had fair outcome and one (5%) case had a poor outcome. A study conducted by the Zakei et al (2018) observed that end results was excellent in 59.3%, good in 37%, and fair in 3.7% of patients participated in the study.…”
Section: Figure 4: Xray Images Of a Case Of Tibial Plateau Managed Wimentioning
confidence: 98%
See 2 more Smart Citations